PENGEMBANGAN PRODUK KULINER LOKAL UNTUK MENINGKATKAN PARIWISATA DAERAH: (Studi Kasus Produk Kuliner Lokal di Wonobodro) - Ardaneswari Kenlarasati; Via Laila Khairunisa; Selfi Nirmalasari; Muhammad Taufiq Abadi (Jurnal Nusantara Berbakti, 2023)
A tourist village is a village that is used as a tourist attraction because of its attractiveness. The potential possessed by the village is a form of integration between attractions, accommodation and supporting facilities which are then presented in a structure of community life. This method by conducting PKM activities in a research-based community service program was carried out on June 18, 2023 in collaboration with UMKM Wonobodro Village, Blado Kab. Batang, which was held at a religious tourism site. This community service activity carries the theme of developing local culinary products to increase regional tourism. Therefore, the tourist village is usually made in one particular area supported by attractions, accommodation, and other facilities which as a whole integrate all elements in a village to promote local uniqueness and wisdom. Culinary tourism is one of the tourism potentials in this tourist village is Opak Singkong. This cassava opak is sold in raw or fried form. Opak is sold from Rp5-10 thousand per pack that can be used as souvenirs for tourists who come.